2020
DOI: 10.1017/gmh.2020.12
|View full text |Cite
|
Sign up to set email alerts
|

Expressions of psychological distress in Sierra Leone: implications for community-based prevention and response

Abstract: Background Over recent decades there has been considerable mental health research in Sierra Leone but little on local conceptualisations of mental health conditions. Understanding these is crucial both for identifying the experienced needs of the population and utilising relevant community-based resources to address them. This study took a grounded approach to identify the ways in which adults in Sierra Leone express psychological distress. Methods Rapid ethnographic methods deployed inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…Thirty signs of distress (listed in Appendix 1, Supplementary Information) were identified (Horn et al, 2020). For the purpose of this paper, the most frequent six signs of distress were analysed.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thirty signs of distress (listed in Appendix 1, Supplementary Information) were identified (Horn et al, 2020). For the purpose of this paper, the most frequent six signs of distress were analysed.…”
Section: Resultsmentioning
confidence: 99%
“…This means that continuing with constructive activity requires considerable motivation, especially when the income generated is small. A failure to continue with these activities (work, study, farming, business) was identified as a common sign of psychological distress in another phase of this project (Horn et al, 2020), which suggests that a person's engagement in work and other forms of constructive activity is not seen purely as a reflection of the economic situation in the country, but rather as an indicator of the individual's emotional wellbeing. In the same study, withdrawing from people ('stays indoors or isolates self; disconnects from people, stops going to public gatherings including mosque or church') was also identified as a key sign of psychological distress.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The study described here does not follow this pattern; instead it aims to measure ‘signs of distress’ without drawing any conclusions about clinical significance, or trying to equate experiences of distress with clinical diagnoses such as depression, anxiety of post-traumatic stress disorder. This decision is partly made as a result of the first phase of data collection, from which no clear ‘syndromes’ or local disorders emerged [ 22 ]. However, it is also heavily influenced by the recent Lancet Commission on Global Mental Health [ 42 ], which recognises that ‘the binary approach to the diagnosis of mental disorders—although useful for health professionals—does not adequately reflect the dimensional nature of mental health or the experience of people affected’ (p4).…”
Section: Discussionmentioning
confidence: 99%
“…The 30 signs of distress to be included in the tool were identified in an earlier qualitative phase of work which has been described elsewhere [ 22 ]. It was based on the ‘rapid ethnographic’ approach developed by Bolton and colleagues [ 15 , 18 ] and included freelisting, key informant interviews and pile sorts.…”
Section: Methodsmentioning
confidence: 99%